Adult education in Latin America: An approach from critical modernity - Osorio Vargas, Jorge (1993)
The text that we present on this occasion is a serious and coherent contribution to the definition of the adult education agenda in Latin America. Based on a large amount of sociological, political and institutional background, it offers us a very pertinent interpretation of the evolution of adult education in our region. At the same time, it presents a set of strategic orientations that inspire a programmatic definition for institutions and practitioners of adult education.